A Transcriptome Analysis: Various Reasons of Adverse Pregnancy Outcomes Caused by Acute Toxoplasma gondii Infection - Zhou, Xue; Zhang, Xiu-Xiang; Mahmmod, Yasser S.; Hernandez, Jorge A.; Li, Gui-Feng; Huang, Wan-Yi; Wang, Ya-Pei; Zheng, Yu-Xiang; Li, Xiu-Ming; Yuan, Zi-Guo (Frontiers in Physiology, 2020)
Background: Toxoplasma gondii (T. gondii) is an obligate intracellular parasite, that can affect the pregnancy outcomes in infected females by damaging the uterus, the intrauterine environment, and hypothalamus and causing hormonal imbalance. However, the molecular mechanisms underlying parasite-induced poor pregnancy outcome and the key genes regulating these mechanisms remain unclear. Therefore, this study aimed to analyze the gene expression in mouse uterus following acute infection with T. gondii RH strain. Three groups of female mice were intraperitoneally injected with tachyzoite three days before pregnancy (FBD6), after pregnancy (FAD6), or after implantation (FID8) as the experimental groups, while three control groups were injected with the normal saline at the same time. Transcriptome analysis of total RNA extracted from infected and uninfected mouse uterus samples was performed using RNA sequencing (RNA-Seq). Results: The three experimental groups (FBD6, FAD6, and FID8) had a total of 4,561, 2,345 and 2,997 differentially expressed genes (DEGs) compared to controls. The significantly upregulated and downregulated DEGs were 2,571 and 1,190 genes in FBD6, 1,042 and 1,303 genes in FAD6 and 1,162 and 1,835 genes in FID8 group, respectively. GO annotation and KEGG pathway analysis showed that DEGs were mainly involved in anatomical structure development, transport, cell differentiation, embryo development, hormone biosynthetic process, signal transduction, immune system process, phagosome, pathways in cancer, and cytokine-cytokine receptor interaction pathways. Conclusions: T. gondii infection can induce global transcriptomic changes in the uterus that may cause pregnancy hypertension, destruct the intrauterine environment, and inhibit the normal development of the placenta and embryo. Our results may help to understand the molecular mechanisms of the acute T. gondii infection, which could promote the development of a new treatment for toxoplasmosis in pregnancy.